Intra-limb variability and inter-limb asymmetry in gymnastics jump tests - Moresi, M.; Bradshaw, E. J.; Thomas, K.; Greene, D.; Braybon, W. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The inter-limb symmetry of loading patterns during drop landings and the first contact of rebound jumps was examined in young, talent-selected female gymnasts. Each gymnast performed three trials of each task from two box heights (72 and 107 cm) onto two Kistler force platforms. A symmetry index and coefficient of variation was calculated from the peak ground reaction forces. The loading patterns for each gymnast was categorised as either symmetrical, significant asymmetry or inconclusive asymmetry. Landing forces increased with age for the 107cm landing task. Approximately 40-45% of gymnasts displayed inter-limb asymmetry across both tasks and heights. Low incidences (12-17%) of inconclusive asymmetry were observed, where the asymmetry observed was less than the intra-limb loading variability.